PERSEPSI GURU TENTANG PELAKSANAAN FUNGSI KEPALA SEKOLAH SEBAGAI MOTIVATOR DI SEKOLAH MENENGAH ATAS NEGERI (SMA N) KOTA SAWAHLUNTO - Thasa Tesia Widasuari (Universitas Negeri Padang, 2013)
The goal of this research are to get information about perception teacher the act of headmasters function as motivator. The population is one hundred and one teachers. And the sample is fivety one teachers, that taken by random sampling technic. The instrument of this research is question with Likert scale models that had tested for validity and reliability. Data analyzed using mean score . The result of this research are perception teacher about the act of headmasters function as motivator in Public High School Sawahlunto City stay is Good Enough. Keywords: Perception Teacher The act of headmasters function as motivator